Proposta de um planejamento estratégico: o caso da granja de ovos certificados - Goetz, Isadora Menegat (2024)
This study aims to propose a strategic plan for the Varela Egg Farm, located in the city of Serafina Corrêa – RS, which differentiates itself from certified eggs in the market. Methodologically, the research is characterized as descriptive-exploratory with a qualitative approach. Data was collected through a questionnaire administered to suppliers, employees, customers, managers, and stakeholders, and the data was analyzed using content analysis techniques. The results demonstrate that the company has a strategic positioning focused on maintenance, showcasing many strengths that highlight its mission in the sector, producing a differentiated product that guarantees acceptable quality standards valued by consumers. This production and marketing trajectory is supported by the proposed mission and vision, as well as a set of objectives, goals, strategies, and action plans that guide future strategic decisions, which must be implemented and controlled by management.